Democracy and human development: issues of conceptualization and measurement. Issue 2 (17th February 2021) - Gerring, John; Knutsen, Carl Henrik; Maguire, Matthew; Skaaning, Svend-Erik; Teorell, Jan; Coppedge, Michael
ABSTRACT: This study attempts to reconcile competing positions in an important debate about the relationship between regime type and human development. We contend that this empirical relationship is contingent upon issues of conceptualization and measurement in democracy. First, the relationship is more likely to be perceived when democracy is measured in a nuanced fashion, taking account of gradations of democracy and autocracy. Second, some aspects of democracy – those associated with competitive elections – are more strongly associated with human development than others. Third, the components of electoral democracy interact in a reinforcing manner. Finally, the impact of democracy on human development is a distal relationship that depends upon a country's entire regime history. Our approach draws on several new datasets that interrogate change across a century, enhancing empirical leverage on this important question. To measure human development, we employ the Gapminder project, covering most sovereign countries from 1900 to 2012. To measure democracy, we draw on Varieties of Democracy data, which measure democracy in a highly differentiated fashion for most sovereign countries from 1900 to the present. An extensive set of analyses offer strong corroboration for the argument.